Regional Financial Analysis and Strategy to Increase Regional Revenue - Al Finna, Siti Tahta; Lutfillah, Novrida Qudsi; Ernawati, Widi Dwi (Equity: Jurnal Akuntansi, 2024)
This study analyzes the regional financial performance and revenue enhancement strategies of the Regional Finance Agency of Trenggalek Regency for the period 2019-2023. Qualitative methods were used with analysis techniques including revenue budget variance analysis, regional original revenue (PAD) effectiveness ratio, regional financial efficiency ratio, and expenditure efficiency ratio. The results showed that the regional financial analysis in 2019-2023 in BKD Trenggalek Regency with the results of (1) revenue realization exceeds the budget target, indicating good budget performance; (2) PAD effectiveness is quite good, although some targets are not achieved; (3) regional financial efficiency is still low due to high regional expenditure; (4) expenditure efficiency is generally achieved with a ratio below 100%; (5) revenue enhancement strategies are implemented through intensification and extensification.